Quaternary Capped In(Ga)As/GaAs Quantum Dot Infrared Photodetectors From Materials to Devices - Adhikary, Sourav (Springer Singapore, 2018)
This book introduces some alternative methods for enhancing the performance of In(Ga)As/GaAs-based quantum dot infrared photodetectors (QDIPs). In(Ga)As/GaAs-based QDIPs and focal plane array (FPA) cameras have wide application in fields such as military and space science. The core of the study uses a combination of quaternary In0.21Al0.21Ga0.58As and GaAs spacer as a capping layer on In(Ga)As/GaAs quantum dots in the active region of the detector structure. For the purposes of optimization, three types of samples growths are considered with different capping thicknesses. The results presented include TEM, XRD and photoluminescence studies that compare combination barrier thickness and its effect on structural and optical properties. Compressive strain within the heterostructure, thermal stability in high temperature annealing, spectral response, shifts in PL peaks peak,and responsivity and detectivity are all considered. The results also present a narrow spectral width that was obtained by using InAs QDs which is very useful for third generation FPA camera application. The book details effect of post-growth rapid thermal annealing on device characteristics and methods to enhance responsivity and peak detectivity. The contents of this book will be useful to researchers and professionals alike.